Study of Traditional Acehnese House Architecture as a Religious Tourism Destination - Annisa, Astrid (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2023)
Traditional Acehnese houses are traditional houses of the Acehnese people that reflect the richness of culture and Islamic values. Traditional Acehnese houses, or commonly called rumoh Aceh, have unique characteristics that can attract tourists, especially those interested in spiritual tourism. In addition to visual appeal, Rumoh Aceh also provides space for religious tourists to engage in spiritual practices and understand the Islamic philosophy that underlies the layout of the house. This enriches the tourist experience with direct interaction with the religious life of the local community. The design of the house oriented towards the direction of the Qibla, the use of natural materials such as wood and rumbia leaves, and architectural elements such as low doors that symbolize humility, all reflect religious and social values ​​that are integrated into the lives of the Acehnese people. This study uses qualitative methods through direct observation and also literature studies on Acehnese architecture and Islamic values ​​integrated into the design of rumoh Aceh. This study emphasizes the importance of preserving Rumoh Aceh not only as a physical cultural heritage, but also as part of Aceh's spiritual identity. The preservation of this traditional house has great potential to contribute to the development of sustainable religious tourism that can support local economic growth, while maintaining the richness of Acehnese culture. Proper promotion and preservation efforts for Rumoh Aceh as a religious tourism object can increase global awareness of Aceh's cultural values ​​and strengthen its position in the religious tourism sector.